Effect of date flesh fiber concentrate addition on bread texture - Borchanı, C.; Blecker, C.; Attıa, H.; Masmoudı, M.; Besbes, S. (Fırat University, 2015)
Composition of second-grade dates from the potential Tunisian cultivars “Deglet Nour” was similar to that of commercial dates. In fact, date flesh could present a value addition by extraction and use of date flesh fiber concentrate in bread formulation. Date flesh fiber concentrate (DFFC) of Deglet Nour variety was extracted and dried at 40 °C. This concentrate was added to wheat flour bread at 0.5%, 1%, 2% and 3% levels to increase the dietary fiber content. The effect of DFFC addition on the textural properties of bread during storage at 25 °C was investigated. In most cases, addition of DFFC did not affect significantly the water activity (aw) values of crumb. During storage of breads, a significant reduction in aw was observed in fortified breads with 1% and 3% levels of fibers. Besides, fresh bread (day-0) and stale bread (days-2) showed a significant increase in firmness of crumb whatever the addition level of fibers. Incorporation of DFFC in bread formulation could give an interesting value addition to date fleshes. This fact is of great economic interest owing to applications of DFFC in the food, pharmaceutical and medicinal industries.